Brand identity and online self-customisation usefulness perception. Issue 13 (1st September 2016) - He, Hongwei; Harris, Lloyd C.; Wang, Weiyue; Haider, Kamran
ABSTRACT: Online self-customisation (OSC) enables customers to tailor their preferences to certain product features via a brand-hosted online platform. The recent literature has given increasing attention to how consumers value OSC. However, extant research is characterised by a scarcity of understanding the effects of brand identity and individual differences on consumer responses to OSC. The purpose of this paper is to examine the mediating role of trust and the moderating role of need for uniqueness on the effects of brand identity prestige and brand identity similarity on consumer perceived usefulness of OSC. A field survey, through mall intercept, was conducted to test this conceptual framework. Our findings advance this field by finding that, not only the brand identity and consumer need for uniqueness but also the interaction between them may affect consumers' evaluation of OSC.